2015
DOI: 10.1088/0953-8984/27/43/436002
|View full text |Cite
|
Sign up to set email alerts
|

Structural defects as a factor controlling the magnetic properties of pure and Ti-doped Bi1−xCaxFeO3−x/2multiferroics

Abstract: Recognition of the factors that may significantly affect the multiferroic properties of BiFeO3-based perovskites remains one of the most challenging tasks in condensed matter physics. To reveal the reasons behind the doping-driven instability of the cycloidal antiferromagnetic order in the polar phase of Bi(1-x)Ca(x)FeO(3-x/2), synthesis and investigation of the crystal structure, microstructure, local ferroelectric and magnetic properties of the ceramic samples of Bi0.9Ca0.1Fe(1-x)Ti(x)O(3-δ) (x  =  0.05, 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…It has been found that the pattern of changes in the lattice parameters of the Bi 0.95 Ca 0.05 Fe 1−x Ti x O 3−δ compounds can be interpreted as suggesting the doping-induced elimination of oxygen vacancies at x ≤ 0.05 and the formation of cation vacancies at x > 0.05 [35]. It has also been shown that the readjustment of the defect structure associated with the mechanism of charge compensation in the aliovalent-doped BFO is accompanied by correlated changes in the morphology, ferroelectric/ferroelastic domain structure, and magnetic properties [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the pattern of changes in the lattice parameters of the Bi 0.95 Ca 0.05 Fe 1−x Ti x O 3−δ compounds can be interpreted as suggesting the doping-induced elimination of oxygen vacancies at x ≤ 0.05 and the formation of cation vacancies at x > 0.05 [35]. It has also been shown that the readjustment of the defect structure associated with the mechanism of charge compensation in the aliovalent-doped BFO is accompanied by correlated changes in the morphology, ferroelectric/ferroelastic domain structure, and magnetic properties [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…The results support the conclusions of the It has been recently shown that the magnetic properties of BiFeO 3 -based multiferroics can be influenced by structural defects. [16][17][18][51][52][53] Indeed, even a small deviation from the ideal cation-anion stoichiometry that results in the appearance of lattice defects can trigger the removal of the cycloidal magnetic order, thus giving rise to a weak ferromagnetic behavior. 54 Taking into consideration that the distribution/concentration of the defects affects the ferroelectric domain structure of a material, 55 The magnetic structure of BiFeO 3 is stabilized by the antisymmetric Dzyaloshinskii-Moriya (DM) interaction of the form…”
Section: 42mentioning
confidence: 99%
“…The origin of the Ca 2+ substitution-driven instability of the cycloidal order has been shown to be closely connected with the charge-compensatory mechanism that involves the formation of anion vacancies in the acceptor-doped materials. [16][17][18] Nevertheless, the doping-introduced lattice defects seem not to be the only factor determining the evolution of magnetic properties in the Bi 1Àx Ae x FeO 3Àx/2 series. Indeed, the Bi 1Àx Ba x FeO 3Àx/2 ferroelectrics have been proven to be antiferromagnetic, thus suggesting that the size of an alkali-earth substituent should also play an important role.…”
mentioning
confidence: 99%
“…The effects of A/B-site substitution from rare earth, alkaline earth to transition metal ions have been also investigated in order to modify the multiferroic properties of BFO ceramics. [14][15][16][17][18][19][20][21] The enhanced magnetization in BFO has been obtained by the destruction of cycloid spin structure through structural transitions and size effects induced by rare-earth ions substitution. [3,4,12,16,17,22] Accompanying with the change of Fe-O-Fe angle, the increased magnetic moment in rare earth (from La to Eu) ions doped BFO has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Among different technologies, the element substitution into BFO ceramics is the generally adopted method which can effectively suppress the volatilization of Bi element and stabilize the crystal structure. The effects of A/B‐site substitution from rare earth, alkaline earth to transition metal ions have been also investigated in order to modify the multiferroic properties of BFO ceramics . The enhanced magnetization in BFO has been obtained by the destruction of cycloid spin structure through structural transitions and size effects induced by rare‐earth ions substitution .…”
Section: Introductionmentioning
confidence: 99%